Terpinen-4-ol and carvacrol affect multi-species biofilm composition - Maquera Huacho, Patricia Milagros [UNESP]; Rodriguez Herrero, Esteban; Verspecht, Tim; Pauwels, Martine; Marcantonio, Elcio [UNESP]; Palomari Spolidorio, Denise Madalena [UNESP]; Teughels, Wim (Taylor & Francis, 2019)
The aim of this study was to investigate the cytotoxic activity and inhibitory effect of terpinen-4-ol (T4ol) and carvacrol against single- and multi-species biofilms. The toxicity of each compound was tested on oral keratinocytes and evaluated by XTT assay. Inhibition and eradication of single-species biofilms were analyzed by crystal violet assay and the effect on multi-species biofilm composition was evaluated by qPCR. T4ol and carvacrol did not affect the epithelial cell viability, in contrast to chlorhexidine, which showed a high cytotoxic effect. Inhibition and eradication of single-species biofilms treated with T4ol and carvacrol were observed. The same inhibitory effect was observed for multi-species biofilms, especially on periodontal pathogens. In conclusion, specific concentrations of T4ol and carvacrol without toxicity towards the epithelial cells reduced the numbers of periodontal pathogens in single- and multi-species biofilms.
Keywords: carvacrol; multi-species biofilm; peri-implantitis; periodontal disease; Terpinen-4-ol